Serum MicroRNA Profiling and Bioinformatics of Patients with Spleen-Deficiency Syndrome. (23rd November 2016) - Yang, Ze-Min; Chen, Long-Hui; Hong, Min; Chen, Ying-Yu; Yang, Xiao-Rong; Tang, Si-Meng; Yuan, Qian-Fa; He, Zhen-Yu; Chen, Wei-Wen
Abstract : To investigate serum microRNA (miRNA) profile and bioinformatics of patients with spleen-deficiency syndrome (SDS) and explore pathogenesis of SDS patients from miRNA levels, 10 patients with type 2 diabetes mellitus (T2DM), within which 5 patients were with SDS and the remaining were with blood stasis syndrome (BSS), and 5 healthy volunteers were recruited. Serum miRNA profiles of SDS patients were identified by quantitative PCR array. Target prediction and functional annotation for miRNAs were performed by miRSystem database. The present study identified 11 candidate serum miRNAs for SDS patients, and their targets were significantly enriched in 18 KEGG pathways and 7 GO molecular functions. Those enriched KEGG pathways included (1) metabolisms of carbohydrate, protein, amino acid, and fatty acid, (2) signaling pathways of insulin, ErbB, chemokine, calcium, and type II diabetes mellitus, (3) invasions of bacterium, Escherichia coli, and Shigella (Shigellosis), and (4) endocytosis and phagocytosis. Those enriched GO molecular functions were mainly involved in transcription regulation and regulation of metabolism. Our findings might elucidate the pathogenesis of SDS patients with disorders of substance metabolism and hypoimmunity from miRNA levels, as well as providing some miRNA biomarkers for clinical syndrome differentiation of SDS.